2013
DOI: 10.4103/2230-8598.109307
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the healthcare-seeking behavior of mothers regarding their children in a rural community of Darjeeling district, West Bengal

Abstract: Background: An ailing, unresponsive health system and the existing social complexities, with considerable contextual differences, are all pervasive in India. In health, these are manifested as differences in morbidity and mortality, severely affecting child health and survival. Objectives: To fi nd out the possible factors affecting the health-seeking behavior of mothers with regard to their children, in a rural community of Darjeeling district, and the reasons for not seeking curative care for perceived sick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…Several reasons were advanced which ranged from high consultation fee at health facilities to possession of previous prescription, belief in their experience (especially among those with more than 3 children in the household) to the fact that the child was too sick and needed an emergency treatment etc. These reasons are comparable with the ones given by other studies which also included lack of time and inaccessibility of nearby health facilities [22,[28][29][30]33,34]. The lack of time given by a majority of the caregivers was linked to the working status of both parents which did not afford them enough time to visit the physician/health care facility.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Several reasons were advanced which ranged from high consultation fee at health facilities to possession of previous prescription, belief in their experience (especially among those with more than 3 children in the household) to the fact that the child was too sick and needed an emergency treatment etc. These reasons are comparable with the ones given by other studies which also included lack of time and inaccessibility of nearby health facilities [22,[28][29][30]33,34]. The lack of time given by a majority of the caregivers was linked to the working status of both parents which did not afford them enough time to visit the physician/health care facility.…”
Section: Discussionsupporting
confidence: 80%
“…Farooq et al [28] believed that this result was true probably because he felt that the participants appeared to be more proactive as well as showed more concerns in getting information and knowledge about recovering back their child's good health. Education which is often described as a domain part of quality of life and usually providing avery important yardstick for determining household socio-economic status has also been shown to affect mothers' knowledge about self-medication [29][30][31][32][33]. Knopf et al noted that the higher the socioeconomic status of the children's family, or the higher the educational level of the children's mother/caregiver, the more Over The Counter (OTC) medications the children were likely to receive [29].…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies also identified people from lower income group seek either self‐treatment of public health facility, whereas their higher income counterparts with insurance coverage prefer private health facilities 37,38 . Socio‐economic factors like family size, mass media exposure, gender differences, access to sanitation and safe water also found to influence the health seeking behaviour in some other studies 39‐41 …”
Section: Introductionmentioning
confidence: 93%
“…37,38 Socio-economic factors like family size, mass media exposure, gender differences, access to sanitation and safe water also found to influence the health seeking behaviour in some other studies. [39][40][41] However, the majority of the studies were upon segmental population and on rural area, the study of health care seeking behaviour of the population across all strata in the city area was not given proper importance. Addressing this research gap is very important because, since, lack of universal health care access still persists in rapidly urbanized areas, the problem needs more in-depth study for policy recommendations.…”
Section: Health Seeking Behaviour In Developing Countriesmentioning
confidence: 99%
“…Nwosu et al [18] in their study revealed that health seeking behaviour increases with age and deceases at older age. However, Ghosh, Chakrabarti, Chakraborty, et al [19] also shown in their study that education plays a vital role in the utilisation of health care which in turn influences maternal deaths.…”
Section: Introductionmentioning
confidence: 96%